ISSUES OF INTENSIVE TEACHING OF FOREIGN LANGUAGES - G.R. Tolibova (Galaxy International Interdisciplinary Research Journal, 2024)
This article examines the concepts of competence and communicative competence according to scientists and linguists. In language education, the role of communicative competence in teaching and learning a foreign language is studied, as well as the effectiveness of communicative competence in teaching a foreign language. The advantage of communicative competence when teaching a foreign language allows you to create a real communicative situation in the lesson, teach students to meaningfully complete sentences and use real words in speech, characteristic of native speakers.